Azospirillum brasilense: Laboratory Maintenance and Genetic Manipulation. Issue 1 (9th November 2017) - Gullett, Jessica; O'Neal, Lindsey; Mukherjee, Tanmoy; Alexandre, Gladys
Abstract: Bacteria of the genus Azospirillum, including the most comprehensively studied Azospirillum brasilense, are non‐pathogenic soil bacteria that promote the growth of diverse plants, making them an attractive model to understand non‐symbiotic, beneficial plant‐bacteria associations. Research into the physiology and genetics of these organisms spans decades and a range of molecular tools and protocols have been developed for allelic exchange mutagenesis, in trans expression of genes, and fusions to reporter genes. © 2017 by John Wiley & Sons, Inc.